(untitled) (Research, Society and Development, 2021)
Objective: to analyze the development profile of COVID 19 in the states most at risk of illness until March 15, 2021; calculation of the COVID 19 lethality and mortality rates among the highest risk states. Methodology: Descriptive, retrospective and analytical study of the epidemiological data of the states of the red belt at risk of illness until the date of March 15, 2021. In the analysis, we prioritized 04 municipalities with the highest incidence in each state. Results and Discussion: Higher contribution of confirmed cases observed in the Southeast, Northeast, Midwest and North regions, respectively. Of the 13 states, 07 of them in only 04 municipalities contributed with more than 40% of confirmed cases. Mortality rates ranged from 0.07 (Maranhão) to 1.08 (Pará) and lethality rates between states ranged from 1.34 (Amapá and Tocantins) and 2.90 (São Paulo). In the states with the highest concentration of confirmed cases in a smaller number of municipalities, there is the possibility of blocking the disease, through specific actions, and in the states dissemination of the Sars-Cov-2 virus in several municipalities, the tendency to lose control is evident. Conclusion: Suggested control strategies: health education; use of mandatory mask, participation of public and private educators in health education with the families of their students; sanitary barriers on the highways of municipalities that together are above 40% of confirmed cases, use of local health intelligence, which combines contact tracking and rapid tests to mitigate outbreaks of COVID-19, by all managers of the three spheres of government and periodic assessments of the epidemiological picture, so that the strategies implemented continue or are improved.